1988
DOI: 10.1002/1098-2337(1988)14:6<403::aid-ab2480140602>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Is indirect aggression typical of females? gender differences in aggressiveness in 11- to 12-year-old children

Abstract: Gender differences regarding aggressive behaviour were investigated in 167 school children, 11 to 12 years of age, through peer‐rating techniques supported by self‐ratings and interviews. The social structure of the peer groups also was studied. The principal finding was that girls made greater use of indirect means of aggression, whereas the boys tended to employ direct means. Gender differences in verbal aggression were less pronounced. The social structure of peer groups was found to be tighter among girls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
560
3
20

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 727 publications
(624 citation statements)
references
References 13 publications
32
560
3
20
Order By: Relevance
“…More in-depth exploration of such dimensions will depend on the development of adequate theoretical models that take into account the specificity of family influences on boys' and girls' aggressive expression over time. Nonetheless, our finding supports the claim that indirect aggression may be particularly important for understanding aggressive behavior in girls and suggests that adequate assessments of aggression in girls should include both indirect and physical types of aggression [2], [31], [32]. Thorough evaluation of different types of aggression is essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More in-depth exploration of such dimensions will depend on the development of adequate theoretical models that take into account the specificity of family influences on boys' and girls' aggressive expression over time. Nonetheless, our finding supports the claim that indirect aggression may be particularly important for understanding aggressive behavior in girls and suggests that adequate assessments of aggression in girls should include both indirect and physical types of aggression [2], [31], [32]. Thorough evaluation of different types of aggression is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Although aggression has largely been conceptualized as a unitary phenomenon, it has been repeatedly suggested that studies of children's aggression should distinguish between different types of aggressive behavior [1], [2]. More often than not this suggestion has been overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Research was initially directed towards physical and verbal forms of harassment (Olweus, 2001, Heinemann, 1973, Olweus, 1978. Social, or indirect, forms of bullying were identified in the eighties (Lagerspetz et al, 1988). In the 2000s, digital bullying, more usually expressed as "cyberbullying", was identified (Campbell, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…In Norway girls outperform boys in all subject, except from physical education (Bakken et al, 2008). In the case of bullying, there is a general tendency for boys to be more involved both as bullies and victims at all ages (Wendelborg et al, 2014, Seals and Young, 2003, Erdur-Baker, 2010, Salmivalli and Nieminen, 2002However, some researchers have found that girls are more involved in indirect or social bullying (Lagerspetz et al, 1988, Björkqvist et al, 1992, but this findings is not consistent (Craig et al, 2009). In the case of cyberbullying, no clear effect of either gender og age is found, although some findings suggest that that girls are more at risk of being targeted (Tokunaga, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Björkqvist, & Peltonen, 1988; Österman, Björkqvist, Lagerspetz, Kaukianen, Landau et al, 1998;Richardson & Green, 1999;Russell & Owens, 1999;Salmivalli et al, 2000), but more recent data suggest the picture is not quite so clear. A meta-analysis of sex differences in aggression in "real-world" settings (Archer, 2004) indicated that greater indirect aggression by females was a function of the method used, with the largest effect sizes obtained with observational methods (d =−.74), followed by peer ratings (d =−.19), and teacher reports (d = −.13).…”
Section: Introductionmentioning
confidence: 99%